Identification of potential novel proteomic markers of Leishmania spp.-derived exosomes - da Silva Lira Filho, Alonso; Lafleur, Andrea; Marcet-Palacios, Marcelo; Olivier, Martin (Frontiers in Cellular and Infection Microbiology, 2024)
Introduction Extracellular vesicles (EVs) are heterogenous cell-derived membrane-bound structures which can be subdivided into three distinct classes according to distinct morphological characteristics, cellular origins, and functions. Small EVs, or exosomes, can be produced by the protozoan parasite Leishmania through the evolutionarily conserved ESCRT pathway, and act as effectors of virulence and drivers of pathogenesis within mammalian hosts. Techniques for the identification of EVs of non-mammalian origin, however, remain inaccurate in comparison to their well-characterized mammalian counterparts. Thus, we still lack reliable and specific markers for Leishmania-derived exosomes, which poses a significant challenge to the field. Methods Herein, we utilized serial differential ultracentrifugation to separate Leishmania-derived EV populations into three distinct fractions. Nanoparticle tracking analysis and transmission electron microscopy were used to validate their morphological characteristics, and bioinformatic analysis of LC-MS/MS proteomics corroborated cellular origins and function. Discussion Proteomic data indicated potential novel proteic markers of Leishmania-derived exosomes, including proteins involved in endosomal machinery and the ESCRT pathway, as well as the parasitic phosphatase PRL-1. Further investigation is required to determine the specificity and sensitivity of these markers.